Erfolg durch nachhaltiges Energie- und Ressourcenmanagement - Posch, Wolfgang; Vorbach, Stefan; Zsifkovits, Helmut; Feichtinger, Gerald (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The contributions of the 10th congress "Sustainability Management for Industries" (SMI) deal very comprehensively with the opportunities but also the challenges and risks of the European energy transformation. In particular, issues in the environment of sustainable logistics, sustainability reporting and assessment from the perspective of companies, strategy and decision-making, corporate governance and energy supply in various sectors of industry are addressed. In this book, the articles are distributed across the core topics of "Supply Chain", "ESG", "Climate Neutrality" and "Energy Transformation".With contributions byJosef Baumüller | Martin Beermann | Hubert Biedermann | Gerald Feichtinger | Michael Friedmann | Günter Getzinger | Lukas Höber | Sandra Heymann | Holger Hoff | Alfred Hypki | Hans-Jürgen Kastner | Wolfgang Kersten | David Kiklhorn | Sigrid Koloo | Bernd Kuhlenkötter | Ladislaus Lang-Quantzendorff | Ingo Leusbrock | Philipp Miklautsch | Wolfgang Posch |Johannes Prior | Rudolf Raunig | Michael Salzmann | Martin Schönberg | Magdalena Schmidbauer | Walter Schwaiger | Carina Seidnitzer-Gallien | Karin Tschiggerl | Birgit von See | Michael Wolny | Manuel Woschank | Jakob Zeilinger | Marlis Zöhrer